Low-Pressure Membrane for Water Treatment Applications - Huda AlFannakh; Heba Abdallah; S. S. Ibrahim; Basma Souayeh (International Journal of Polymer Science)
Three ultrafiltration membranes were prepared using phase separation techniques. The membranes were characterized by scan electron microscope, porosity, pore size distribution measurement, and mechanical properties. The membrane performance was carried out using synthetic solutions from humic acid and tap water to express the contaminated drinking water. The polyvinylidene difluoride (M2) has the highest tensile strength 33.2 MPa with elongation of 52.3%, while polyacrylonitrile (M3) has the lowest mechanical properties, tensile strength 16.4 MPa with elongation of 42.7%. Polyethersulfone membrane (M1) provides the highest removal of humic acid, which was 99.5, 98.8, and 98.2% using feed concentrations 0.1, 0.3, and 0.5 g/l, respectively, while M3 provides the highest permeate flux which was 250, 234.4, and 201.4 l/m2 h using feed concentrations 0.1, 0.3, and 0.5 g/l, respectively. Analysis of water samples indicates that the prepared membranes can be used to treat the contaminated drinking water which produced the high quality of drinking water after treatment.